A comparative study of raw, acid-modified and EDTA-complexed Acacia auriculiformis biomass for the removal of hexavalent chromium. Issue 4 (20th April 2020) - Shahnaz, Tasrin; Patra, Chandi; Sharma, Vivek; Selvaraju, N.
ABSTRACT: This study deals with the elimination of hexavalent chromium from simulated solution using Acacia auriculiformis shells and its different modified forms as potent biosorbents. The raw plant biomass (RAA) was modified with sulphuric acid and named as sulphuric acid-activated carbon (SAA) and was further complexed with a chelating reagent ethylenediaminetetraacetic acid (SAAC) to further modify its sorption capacity. Adsorption parameters like pH, adsorbent dosage, temperature and initial metal concentration were optimised in batch study. The optimised data were further equilibrated using isotherm, kinetic and thermodynamic models to determine the nature of the sorbent–sorbate interaction. Langmuir isotherm showed the best fit with maximum Langmuir adsorption capacities being 91.48, 117.75 and 145.72 mg/g for RAA, SAA and SAAC respectively at pH 2. From the correlation coefficients of the fitted kinetic models, the sorbent–sorbate interaction followed pseudo-second order and is chemisorption in nature. Thermodynamic analysis verifies endothermic interaction with elevated degree of randomness. The adsorbents were regenerated for four cycles and the biosorbents proved potent for efficient sorption of Cr(VI). For SAAC, the removal efficiency decreased from 57.51% to 26.81% after fourth cycle which is more than twice and thrice as compared to SAA and RAA. GRAPHICAL ABSTRACT: